The impact of aging on morphometric changes in the cerebellum: A voxel-based morphometry study - Stalter, Johannes; Yogeswaran, Vinuya; Vogel, Wolfgang; Sörös, Peter; Mathys, Christian; Witt, Karsten (Frontiers in Aging Neuroscience, 2023)
Aging influences the morphology of the central nervous system. Whereas previous studies focused on morphometric changes of the supratentorial parts, investigations on age-related cerebellar changes are rare. The literature is heterogenous about the morphological changes in the cerebellum depending (i) on the methods used (cerebellar analysis in the context of a whole brain analysis or specific methods for a cerebellar analysis), (ii) the life span that was investigated and (iii) the analytic approach (i.e. using linear or non-linear methods). We fill this gap, investigating age dependent cerebellar changes in the aging process occurring before the age of 70 in healthy participants, using non-linear methods and the SUIT toolbox which is specifically developed to examine the cerebellum. Furthermore, we relate our findings to functional maps of the cerebellum for an overview of the possible behavioral correlates. Twenty-four older participants (mean age 64.42 years, SD4.8) and twenty-five young participants (mean age 24.6 years, SD2.14) were scanned using a 3T-MRI. Data were processed using a spatially unbiased infratentorial template toolbox (SUIT). Grey matter (GM)-volume loss was found in older participants in three cluster in the right cerebellar region (crus I/II and lobule VI related to the frontoparietal-network, crus I functionally related to the default-mode network and lobule VI extending into vermis VIIa related to the ventral-attention-network). Our results underline an age-related decline in GM-volume in right cerebellar regions functionally predominantly related to non-motor networks and cognitive tasks regions of the cerebellum before the age of 70.